Diversity of cicadomorpha (Hemiptera: Auchenorrhyncha) in Citrus orchards in Northeastern Argentina - Dellapé, Gimena (2013)
Among phytophagous insects, the Cicadomorpha are important economically because they damage crops by sucking plant sap and by transmitting plant pathogens, such as Spiroplasma citri and Xylella fastidiosa to citrus. In Argentina little knowledge exists about this subject. The aim of this work was to study the diversity of Cicadomorpha associated with citrus orchards in Entre Ríos province, and their seasonal fluctuation in relation with climatic and phenological conditions. A total of 1,554 specimens belonging to 28 species of Cicadomorpha were collected with yellow sticky traps in sweet orange (Citrus × sinensis (L.) Osbeck) and tangerine (Citrus unshiu Marc) orchards. The Shannon index and the Simpson index suggested a similar trend in the distribution of the dominant species in both crops. In the orange orchard, Cicadomorpha populations increased in the summer coincidently with temperature increases. On the other hand, a significant increase in abundance during the winter months was coincident with increase of early sprouts of the citrus plants. Entre Ríos province represents a new distribution record for 13 species. Tangerine is a newly recorded host-plant for 16 species studied, and eight species are reported for the first time on 'Valencia Late' orange.